Determination of Genomic Breed Composition using ADMIXTURE Software - Patel, Komal N.; Patel, Ashish C.; Shah, Heena; Nayee, Nilesh G.; Rank, Dharamshi N. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Information from a reference population of animals with accurate breeding values is used to predict the genetic merit of a test population of animals for which such accurate phenotypic information is not available. For crosses, these procedures may be used to predict the proportion of genes of one breed in crossbred cattle when sets of genotypes from purebred animals are available as a reference. The genomic breed composition in 6326 HF crossbred animals (as a test population) performing in Gujarat was determined from SNPs (single nucleotide polymorphism) genotyped by INDUSCHIP array using ADMIXTURE software. The genotypes of 651 purebred indigenous and 120 exotic animals were used as reference genotype for determination of genomic breed composition. Unsupervised clustering analysis using ADMIXTURE software was carried out to infer ancestry ratios for 250 purebred animals using 14718 pruned INDUSCHIP SNPs. It showed that all the B. indicus animals were assigned to their respective breeds. A supervised clustering using 14718 INDUSCHIP variants was performed to infer breed proportions in 6326 crossbred animals with keeping K value as 9. As several indigenous breeds show evidence of admixture, the screening and selection for admixture in candidate bulls for breed purity can improve breeding programs. The average proportion of exotic inheritance was 55% in crossbred population. Hence, SNP genotyping gives opportunity to determine the exact breed proportions in crossbred animals and will be useful in regulation of exotic inheritance in the crossbred population for the optimum productivity of the animals reared by farmers.
Keywords: ADMIXTURE analysis; Exotic inheritance; Genomic breed composition; HF crossbreds; SNP genotyping